A tale of two curricula: Learning and matching in the final year of medical school - Madrazo, Lorenzo (Canadian Medical Education Journal, 2020)
In this article, I highlight two curricula that I believe are most prominent during the final year of the Canadian medical school experience—that of learning and that of matching to residency. While these two curricula are not mutually exclusive, they can be perceived as contradictory by learners, shifting their focus away from learning towards performing well in an effort to optimize their chance of matching to their program of choice. Moreover, the increasing rates of unmatched students in recent years have likely contributed to this shift while increasing stress and anxiety associated with this final year. In addition to curricular reform, I argue that there needs to be curricular consistency among all stakeholders including undergraduate programs, postgraduate programs, and other third-party organizations.